2018
DOI: 10.1590/s2175-97902017000400176
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and physicochemical characterization of meloxicam orally fast disintegration tablet using its solid dispersion

Abstract: Meloxicam (MLX) is a non-steroidal, anti-inflammatory drug that is prescribed in the treatment of rheumatoid arthritis and osteoarthritis. MLX is practically insoluble in water and exhibits a slow onset of action. In this study, MLX solid dispersions (MLX SDs) were prepared to improve the water solubility of this poorly water-soluble drug. Then orally disintegrating tablets (ODT) of MLX were developed using MLX SD to decrease the onset of action of this drug. MLX, poloxamer 188, and crospovidone of different r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 23 publications
2
6
0
1
Order By: Relevance
“…Finally, in mixtures of δ 1+2 < 30.0 MPa 4) exhibits an endothermic peak corresponding to the meloxicam melting as original sample with on-set temperature of 524.0 K and peak temperature of 535.4 K. This last value is similar regarding some other values reported in the literature, i.e. 535.0 K, 38 535.2 K, 39 535.7 K, 40 536.1 K, 41 and 536.7 K. 29 However, some significant differences are observed regarding the values reported by Sathesh-Babu et al (530.0 K), 32 44 which also differ significantly regarding our peak value. X-ray diffraction spectra for meloxicam as original sample and after saturation in neat water, neat 2-propanol and the aqueous mixture of x 1 = 0.50 are shown in Figure 5.…”
Section: Resultssupporting
confidence: 85%
“…Finally, in mixtures of δ 1+2 < 30.0 MPa 4) exhibits an endothermic peak corresponding to the meloxicam melting as original sample with on-set temperature of 524.0 K and peak temperature of 535.4 K. This last value is similar regarding some other values reported in the literature, i.e. 535.0 K, 38 535.2 K, 39 535.7 K, 40 536.1 K, 41 and 536.7 K. 29 However, some significant differences are observed regarding the values reported by Sathesh-Babu et al (530.0 K), 32 44 which also differ significantly regarding our peak value. X-ray diffraction spectra for meloxicam as original sample and after saturation in neat water, neat 2-propanol and the aqueous mixture of x 1 = 0.50 are shown in Figure 5.…”
Section: Resultssupporting
confidence: 85%
“…DSC study of pure drug (Figure 3) showed sharp exothermic peak at 162.17°C corresponding to melting point of drug indicating crystalline nature. As per result stated by author Zahra Shoormeij et al 25 in his research work, Poloxamer 188 showed sharp endothermic peak at 60.6°C, indicating its melting. Spray dried microparticles D4 in ratio 1:4 w/w ( Figure 4) prepared using Poloxamer 188 does not showed melting peak of Poloxamer 188 suggesting uniform distribution of polymer.…”
Section: Differential Scanning Calorimetry (Dsc)supporting
confidence: 59%
“…X-ray diffraction of pure drug DHA ( Figure 5) showed sharp peaks with diffraction angles (2θ) at 25.43 0 , 25.45 0 , 25.47 0 and 25.49 0 with peak intensity of 2138, 2109, 2005 and 1958 respectively signifying substantial crystallinity of drug. Poloxamer 188 showed characteristic peak at 18.83 0 and 22.86 0 with peak intensity 2504 and 2857 indicating crystallinity 25 . Spray dried microparticles ( Figure 6) showed peaks at 25.43 0 , 25.45 0 , 25.47 0 and 25.49 0 with peak intensity of 670, 670, 668 and 646 respectively.…”
Section: X-ray Powder Diffraction (Xrpd)mentioning
confidence: 99%
“…However, the poorly aqueous solubility and wettability of ME resulted in a slower dissolution rate of the drug, and hence, a lower oral bioavailability concomitant with slowing its onset of action [ 33 , 34 ]. Enhancing the aqueous solubility of ME could facilitate its oral absorption and bioavailability and reduce its onset of action for the treatment of different types of acute pain [ 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%